2021
DOI: 10.1136/bmjopen-2021-050444
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of and symptom findings from an online symptom check-in tool for COVID-19 outpatient follow-up among a predominantly healthcare worker population

Abstract: IntroductionHealth systems worldwide have had to prepare for a surge in volume in both the outpatient and inpatient settings since the emergence of COVID-19. Early international healthcare experiences showed approximately 80% of patients with COVID-19 had mild disease and therfore could be managed as outpatients. However, SARS-CoV-2 can cause a biphasic illness with those affected experiencing a clinical deterioration usually seen after day 4 of illness.ObjectiveWe created an online tool with the primary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…During the extraordinary situation of the COVID-19 pandemic, remote telemonitoring has been quickly implemented in different ways [5][6][7][10][11][12][13]. In general, many patients and health care professionals are very positive about this concept.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 3 more Smart Citations
“…During the extraordinary situation of the COVID-19 pandemic, remote telemonitoring has been quickly implemented in different ways [5][6][7][10][11][12][13]. In general, many patients and health care professionals are very positive about this concept.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Remote telemonitoring is used for conducting disease triage; reducing hospital admissions; and providing reassurance, disease and disease course information, and psychological support to clinically stable patients at home. Several studies have reported that patients appreciate all forms of remote telemonitoring (eg, the measuring of vital parameters, symptom recording, and daily teleconsultations) in various settings (eg, in primary care and after an emergency department visit or hospital admission) [5][6][7][10][11][12][13]. The important aspects are easy access to the program, good information provision, and the good quality of the service for the onboarding process.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of studies have reported moderately high user satisfaction ratings for COVID-19 symptom checkers. One study of 296 patients who were predominantly health care workers reported 56% found their institution’s internal web-based symptom checker tool useful [ 11 ]. Symptom checkers for conditions other than COVID-19 have also reported positive user experiences, including 1 study reporting high satisfaction in 70%-80% of users [ 9 ].…”
Section: Introductionmentioning
confidence: 99%